Pioneer plants consumption by frugivorous bats in a fragment of tropical dry forest (Colombia) (2019)
Seed dispersal is an important process for the regeneration and maintenance of forests; This mechanism allows plants to colonize new sites and maintain the structure of the population. Bats have been recognized as effective dispersers of seeds in several tropical forest ecosystems, due to the ability to defecate in flight, fly over open areas and exert a germination effect on released seeds. In this study was to evaluate diet preference of fruit bats in a tropical dry forest in the department of Tolima. The analysis of 63 dietary records of 14 bat species allowed to identify 11 plant species, three genera and one morphospecies. Bidens pilosa, Piper crassinervium and Physalis peruviana L. showed the highest consumption. Artibeus lituratus had the widest niche breath, followed by Artibeus planirostris. Low overlays were present among these bat species, which could reflect a niche segregation as a strategy to avoid competition between sympatric species. The consumption of fruits in a successional shrubs state is highlighted, which reaffirms the key role of bats in the dispersion of pioneer species.